RELATIONSHIP BETWEEN SELF-REPORTED SLEEP AND DISEASE ACTIVITY DIFFERS BASED ON ENDOSCOPIC OR CLINICAL DISEASE ACTIVITY MEASURES. (22nd January 2022) - Kamp, Kendra; Clark-Snustad, Kindra; Yoo, Linda; Buchanan, Diana; Jacobs, Jeffrey; Barahimi, Mitra; Heitkemper, Margaret; Lee, Scott D
Abstract: BACKGROUND: Patients with inflammatory bowel disease (IBD) report more sleep disturbances than healthy controls. Self-reported sleep disturbances have been associated with active clinical disease. Few studies have examined the relationship between self-reported sleep and endoscopic disease activity, and IBD sleep studies have yet to consider the discrepancies that exist between clinical and endoscopic disease measures. The purpose of this pilot study was to examine self-reported sleep based on endoscopic and clinical disease activity among patients with IBD. METHODS: Patients with IBD were recruited from a single medical center. Patients ages 18-55 with a scheduled endoscopy were included. Patients completed informed consent, wore a wrist actigraph for 10 days, and answered baseline demographic, clinical disease activity, and sleep questionnaires including Patient-Reported Outcomes Measurement Information System (PROMIS) sleep disturbance, PROMIS sleep-related impairment, and the Pittsburg Sleep Quality Index (PSQI). For both the PROMIS and PSQI, higher scores indicate greater sleep/wake disturbances. Endoscopic disease activity (Mayo or Simple Endoscopic Score) within three months was obtained from the medical record. RESULTS: The study included 27 participants with a mean age of 33.3 (SD: 8.2) years and a disease duration of 11 (SD: 7.2) years. The sample predominantly had Crohn's disease (75%) and 61% were female. Sixty-three percent of the total sample were classified as poor sleepers based on the PSQI. When comparing self-reported sleep based on clinical disease activity, patients with active clinical disease had higher self-reported sleep disturbance (57.3 vs. 49.7, D=1.28) and sleep-related impairment (58.1 vs. 52.8, D=0.51) compared to those with inactive clinical disease. However, self-reported sleep and endoscopic disease activity had the opposite interpretation. Only 40% of patients with active endoscopic disease were poor sleepers compared to 76.5% of patients with inactive endoscopic disease. Patients with active endoscopic disease had lower self-reported sleep disturbance (49.2 vs 52.6, D=-0.53) and sleep-related impairment (49.7 vs. 56.6, D=-0.71) compared to those with inactive endoscopic disease. CONCLUSION: The relationship between self-reported sleep and disease activity differs based on the measure of disease activity. Our findings of self-reported sleep disturbances and active clinical disease are similar to previous studies. However, when examining the relationship based on endoscopic disease activity, patients with active endoscopic disease had less self-reported sleep disturbance than patients with inactive endoscopic disease. Further research is needed to better characterize the relationship between sleep and disease activity, and determine the underlying mechanisms related to poor sleep in the IBD population.